Corporate Culture - Haydon, Liam D., author.
1 online resource (204 pages)
Keywords: The corporation – an immortal collective bound to act for the common good – was developed in the seventeenth century, but comparatively little attention has been paid to its literary ramifications. This work combines corporate history with literary analysis to demonstrate how corporations, and the literature they engendered, shaped ideas of the public sphere, trust, the morality of trade and exchange, national identity, and salvation.Drawing on a wide range of genres – including corporate publications, letters, and minute books; dramatic works; epic poetry and sermons – this study shows how widely corporate rhetoric spread, and how embedded it was in the early modern social imagination.